1983
DOI: 10.1136/jnnp.46.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Progressive optic neuropathy and sensorineural hearing loss due to chronic glue sniffing.

Abstract: SUMMARY A 27-year-old male developed cerebral and cerebellar atrophy over a period of five years of extensive glue sniffing. He also developed bilateral optic atrophy with blindness and severe sensorineural hearing loss. Investigation failed to show any other cause for the visual or hearing loss. Peripheral polyneuropathy and central nervous system damage may follow chronic toluene toxicity, but these auditory and visual complications have not previously been described.The acute central nervous system symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(40 citation statements)
references
References 9 publications
0
40
0
Order By: Relevance
“…Toluene ototoxicity has been discus sed previously. Evidence indicating that toluene exposure affects hearing comes mainly from studies conducted with toluene abusers (21)(22)(23)(24) and animal s (8,(27)(28)(29)(30)(31). In rats toluene interacted synergistically with noise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toluene ototoxicity has been discus sed previously. Evidence indicating that toluene exposure affects hearing comes mainly from studies conducted with toluene abusers (21)(22)(23)(24) and animal s (8,(27)(28)(29)(30)(31). In rats toluene interacted synergistically with noise.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is also beginning to accumulate which suggests that an ototra umatic interaction may ex ist between noise and org an ic sol-ve nts. Data on the ototoxic effect s of solvents like tolu ene, xylene, and styr ene come mainl y fro m limited animal studies and ca se report s on subs tance abu sers (19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…29,38 Other causes of morbidity and mortality are related to the specific volatile chemical(s) used, associated health risk behaviors, drug-drug interactions, or additional material(s) found in the various inhaled products. Toxic effects attributed to specific chemicals include an ichthyosis-like dermatitis on the extremities, 25 decreased visual acuity, 41,42 sensorineural hearing loss, 42 cardiomyopathy, 43 toxic hepatitis, 44 distal renal tubular acidosis, 45 metabolic acidosis, 46 leukemia, 47 and aplastic anemia. 48 There is evidence that tolerance, dependence, and withdrawal symptoms can occur, and reported morbidities also include toluene embryopathy and neonatal withdrawal.…”
Section: Mechanism Of Abuse and Immediate Effects Of Inhalantsmentioning
confidence: 99%
“…Thereafter Keane [6] reported on a patient with optic neuropathy due to chronic inhalation of toluene. Since then, toluene-opticoneuropathy has been demonstrated with [7][8][9] and without [3] VECP abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In rare instances ocular disturbances have been produced [4]. Several authors have demonstrated abnormal visual evoked cortical potentials (VECPs) as a result of toluene inhalation [5][6][7][8][9], while only one report included abnormal electroretinogram (ERG) findings of a decreased b-wave [5]. To our knowledge, no report has included results of electrooculogram (EOG) studies.…”
Section: Introductionmentioning
confidence: 99%